Quantum interference of multiple on-chip heralded sources of pure single photons - Spring, J; Salter, P; Mennea, P; Metcalf, B; Humphreys, P; Moore, M; Gates, J; Thomas-Peter, N; Barbieri, M; Jin, X; Langford, N; Kolthammer, W; et al. (Optical Society of America, 2014)
We demonstrate generation of heralded single photons in silica photonic chips with a preparation efficiency of 80% and single photon purity of 0:86. We show multiple indistinguishable photon sources on a single chip with HOM-dip visibilities of up to 95%. © OSA 2014.